Uji Three Point Bending Kawat Nikel Titanium Dimensi 0,010 x 0,030 Inci yang digunakan sebagai retainer - Diva Gama Putri, Salsabila; Hamonangan Nasution, Fajar; Gadih Pratomo, Harris (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Fixed retainer are a practical retention method because they require minimal cooperation from the patient. Fixed reteiner are made from various types of wire, one of which is nickel titanium. However, when using a fixed retention device, several problems arise, such as fracture of the wire, loss of bond between the surface of the wire and composite, failure of attachment of the composite to the teeth, and unexpected tooth movement. Objective: To determine the shape memory and superelastic properties of nickel titanium wire with dimensions of 0.010 x 0.030 inches used as a retention device after a three point bending test. Method: This research is a laboratory experimental study using 5 samples of nickel-titanium wire measuring 0.010 x 0.030 inches. The wire length is 30 mm. The collected data was then tested using a tested. Results: Nickel titanium wire measuring 0.010 x 0.030 inches with a deflection of 1.5 mm shows a graph with a smaller hysteresis than a deflection of 2 mm with a wider hysteresis. Nickel-titanium wire measuring 0.010 x 0.030 inches with a deflection of 1.5 mm and 2 mm shows that the wire experiences permanent deformation before returning to its initial shape, which could be due to the amount of deflection applied exceeding the tensile yield strength range limit of the wire. Conclusion: The amount of deflection given to the nickeltitanium wire samples is 1,5 mm and 2 mm influences the amount of force released. The deflection of a given wire determines how much force can be generated when the wire is applied.